An Optimal Animal Model of Ischemic Stroke Established by Digital Subtraction Angiography-Guided Autologous Thrombi in Cynomolgus Monkeys - Ye, Juan; Shang, Hailong; Du, Hongdi; Cao, Ying; Hua, Lei; Zhu, Feng; Liu, Wei; Wang, Ying; Chen, Siyu; Qiu, Zhifu; Shen, Hailin (Frontiers in Neurology, 2022)
Objective Ischemic stroke seriously threatens human health, characterized by high rates of incidence, disability, and death. Developing a reliable animal model that mimics most of the features of stroke is critical for pathological studies and clinical research. In this study, we aimed to establish and examine a model of middle cerebral artery occlusion (MCAO) guided by digital subtraction angiography (DSA) in cynomolgus monkeys. Materials and Methods Fifteen adult male cynomolgus monkeys were enrolled in this study. Under the guidance of DSA, MCAO model was established by injecting an autologous venous clot into the middle cerebral artery (MCA) via femoral artery catheter. Thrombolytic therapy with alteplase (rt-PA) was given to 8 of these monkeys at 3 hours after the occlusion. Blood test and imaging examination, including computed tomography angiography (CTA), CT perfusion (CTP), brain magnetic resonance imaging (MRI), and brain magnetic resonance angiography (MRA), were performed after the operation to identify the post-infarction changes. The behavioral performance of cynomolgus monkeys was continuously observed 7 days after operation. The animals were eunthanized on the 8th day after operation, and then the brain tissues of monkeys were taken for triphenyltetrazolium chloride (TTC) staining. Results Among the 15 cynomolgus monkeys, 12 of them were successfully modeled, as confirmed by the imaging findings and staining assessment. One monkey died of brain hernia resulted from intracranial hemorrhage confirmed by necropsy. DSA, CTA, and MRA indicated the presence of an arterial occlusion. CTP and MRI showed acute focal cerebral ischemia. TTC staining revealed infarct lesions formed in the brain tissues. Conclusion Our study may provide an optimal non-human primate model for in-depth study of the pathogenesis and treatment of focal cerebral ischemia.